Structural Brain Abnormality in JME - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1999)
An automated and objective technique of statistical parametric mapping was employed in the analysis of structural MRI from 20 patients with juvenile myoclonic epilepsy (JME) and 30 control subjects studied at the Institute of Neurology, London, UK.